Språkvård, a periodical from Svenska Språknämnden - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Språkvård (language cultivation) is a periodical that was published between 1964 and 2007 by Svenska Språknämnden, predecessor of the Language Council of Sweden. Final issue was published beginning of 2007.
1965 - 2/2007

Språkvård är en tidskrift som gavs ut av Språkrådets föregångare Svenska språknämnden. Utgivningsår: 1964 - 2007. Sista numret gavs ut i början av 2007. 1965 - 2/2007.
Svenska språknämndens tidskrift: Språkvård
Keywords: language skills; språkfärdigheter; national languages; nationalspråk; Linguistics; Språkvetenskap; Periodical; Tidskrift [Publikationstyp]; language documentation; språkdokumentation; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur